Microteaching Dalam Pembelajaran Kode Etik Profesi Hubungan Masyarakat Pada Mahasiswa Universitas Sunan Giri Surabaya - Imam Subeki Firmanto; Muhammad Yusron Maulana El-Yunusi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Microteaching is a learning method that aims to train teaching skills on a small scale, where students can hone their communication skills, classroom management, and develop teaching materials effectively. This research aims to examine the application of microteaching in learning the professional code of ethics for public relations among students at Sunan Giri University, Surabaya. The code of ethics for the public relations profession is an important aspect in shaping the professionalism of students who will later enter the world of the public relations industry. Microteaching, as a teaching method that focuses on developing teaching skills in a short time, is expected to increase students' understanding and ability to apply the principles of the code of ethics in professional practice. This research was conducted using kualitative approach to measure the effectiveness of microteaching in improving students' knowledge, skills and attitudes towards the public relations professional code of ethics. The research results show that microteaching can increase students' understanding of the importance of professional codes of ethics, improve their communication skills, and strengthen professionalism in public relations practice. Based on these findings, it can be concluded that microteaching is an effective method for introducing and deepening students' understanding of the public relations professional code of ethics